High-Performance terahertz patch antenna with metamaterials for advanced 6G and biomedical technologies - Younes Siraj; Youssef Khardioui; Kaoutar Saidi Alaoui; Jaouad Foshi (Scientific African)
This paper explores the improvement of terahertz patch antenna performance using metamaterials (MTM) for 6G and biomedical systems. The suggested structure is a slotted patch antenna with a partial ground. Operating at 3.62 THz, the antenna is implemented on a polyimide substrate with a thickness of 4 µm. A MTM of 6 × 5 array of SRR elements is proposed and integrated beneath the antenna. This inclusion results in significant enhancements in various antenna key parameters. The reflection coefficient decreases from -30.85 dB to -42.33 dB, ensuring lower signal loss and optimized data transmission. Furthermore, the radiation pattern exhibits marked advancements, with the antenna gain improving from 3.89 dB to 6.04 dB and the directivity rising from 5.00 dB to 7.54 dB, providing more concentrated radiation. These results demonstrate the capability of MTM to elevate THz patch antenna characteristics for various applications including 6G networks and biomedical imaging systems.